(untitled) (Al-Academy, 2016)
The location element indispensable in the film, it is the container that meets the all the elements of the artwork, and place in the cinema topic or space as the existence of a material perceptible senses, is one of the key elements in the drama because he is one of the conditions to achieve supply drama which, with the nature of the vehicle because it is linked to reality the real and the reality of mental imagined, and returns the importance of the place mentally to change the pattern in the building’s traditional place in the world of the film, is that the space under the facts of the events imagined or mental and determined by the processors directorial, and where mental in the movies but found himself a world with a pace sometimes seems like a different or that he does not belong to the world of film and to the coordinated or private can be considered a displacement towards the creation of a new world is linked to the real world to the place unrealistic, but the bonds are weak Baksidih directorial, and can enter as a party to the conflict Filma figure dramatic has the ability to produce meaning and connotations, all the way to diversity and fascinate the optical and excellence in construction Gaii fiction film of the film. order to fascinate and to change the visual pattern in the traditional construction of the place in the world of movie film